A Qualitative Study on Sexuality and Sexual Experiences in Community Forensic Mental Health Patients in Queensland, Australia - Brand, Elnike; Nagaraj, Dinesh; Ratsch, Angela; Heffernan, Edward (Frontiers in Psychiatry, 2022)
This qualitative study reports on the sexuality and sexual experiences of community-based forensic mental health participants. The findings indicate that these participants feel the need for intimacy and want to engage in sexual activity more often than their neurotypical Australian peers. Participants identified their mental health and the side effects of compliance with prescribed psychotropic medications were barriers to achieving their desired level of sexual activity. Participants supported the notion that mental health teams were positioned to assist patients navigate the psychological, cultural, education and physical barriers to achieving sexual health and wellbeing. We propose several interventions to support these participants and other community forensic mental health patients in attaining healthy relationships, understanding their sexual health, and gaining more fulfilling sexual experiences. These interventions, which include sex education, upskilling in socialisation and communication, and regular medication reviews, could be delivered as part of the holistic care provided by mental health teams. Mental health clinicians should be offered appropriate training to assess patients and have discussions related to sexuality, sexual experiences and sexual health needs.